DESAIN PEMBELAJARAN UNTUK GURU TK INKLUSIF - Suparno . (LPMPP Universitas Negeri Yogyakarta, 2011)
Abstract: Developing an Instructional Design to Improve Kindergarten Teachers’ Competencies in the Perspective of Inclusive Education. This study aims to develop an instructional design set to improve kindergarten teachers’ competencies in inclusive education in terms of pedagogic, personal, social, and professional aspects. It was a research and development study involving the stages of predevelopment, model development, product validation. The sample comprised 34 kindergarten teachers selected by the purposive sampling technique. The results show that: (1) the majority of kindergarten teachers do not understand the concept of inclusive education, (2) a set of indicators of kindergarten teachers’ competencies in inclusive education and a set of competency instruments and instructional design can be produced; (3) the implementation of the instructional design model is capable of increasing kindergarten teachers’ competencies in inclusive education. The instructional design significantly improves kindergarten teachers’ pedagogic, social, and professional competencies, but it does not significantly increase the personal competency. Keywords: inclusive education, kindergarten teachers